Modulation of the hypothalamic-pituitary-adrenal axis by the limbic system of the rat brain [Microfiche] - Daniels, William M. U.(William Mark Uren) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. in Med. Sc.) -- University of Stellenbosch, 1988.